Relations between the Parsis of India and the East India Company (1601-1858) - Jaleh Tajaldini (پژوهش های تاریخی, 2022)
1- Abstract The arrival of Britain in India under the cover of the East India Company at the beginning of the 17th century led to the country’s gaining access to the legendary financial resources in the subcontinent. However, with the British presence in India, the Zoroastrian community of this country, known as the Parsis, also underwent a significant economic transformation. Evidence of the increase in the wealth of the Parsis after the establishment of the British East India Company in the subcontinent is that in the 19th and 20th centuries, with the capital possessed, they set up numerous and large factories in India. Were there any special relations in the economic and professional field between the Parsis of India and the company? This is the question that the present study seeks to answer. In this study, using related historical sources, including works about the Parsis of India as well as compilations about the beginning and implementation of the British East India Company, the reasons for the positive perception of the company leaders of the Parsis are examined using a descriptive-analytical approach. Then, by reviewing the professional life of the Parsis, in two important ports of Surat and Bombay, which were the main points of contact with the company’s employees, examples of the Parsis services to the British East India Company and the privileges donated to the Persis leaders by the British are recounted and analyzed. The results show that the Parsis cooperation with the British government representatives in India was not limited to economic fields and that the British also had the assistance of the Zoroastrian community in the political arena. 2- Introduction The followers of Zoroastrianism have been known in India from past times as “Farsi” or “Parsi”. In fact, since the annexation of the western parts of India to the Achaemenid Empire, Iranians travelled to these areas. Also, Iranian Zoroastrians, especially their clerics, travelled to India before Islam to propagate this religion for business. But the issue of their migration to India after Islam is mainly based on a poetic story called "Qeṣṣe-ye Sanjān" composed in 1008 AH (1600 AD). The narrator of the story events has been a trusted Zoroastrian priest to Bahman Keyqubad, the story’s composer. Based on this source, after the Arab invasion of Khurasan during the conquest of Iran, the Zoroastrians of a village called Sanjan in north-eastern Iran took refuge in the nearby mountains and spent a hundred years there. Then, they travelled to the island of Hormuz and lived there for fifteen years. "Dib" on the southern shores of the Indus was their next destination, where they remained for nineteen years. Then, they moved to Gujarat and settled in an area that was reminiscent of the former land of Sanjan, where they also spent five hundred years. Therefore, this group of immigrants left India in the middle of the second century AH. The question is, how did the narrator get these exact time intervals? The editor of Qesse in the introduction of the book indicates the existence of sufficient references to prove the truth of this story. One of the documents he presents is the narration of Baladhuri in "Futuh al-Buldan" in which the people of Kerman fled from the Arab army. But this narration is not applicable to the story of Sanjan. The narration of Baladhuri indicates the escape of a number of people of Kerman in the first half of the first century AH from the Arab army and their departure to Hormuz and the conflict with the Arabs on this island. Baladhuri's words in this regard end with this report: many people of Kerman fled by sea. The existence of many ambiguities in the story caused its rejection by some contemporary Zoroastrian scholars. However, the story says the adventure of the Parsis refugees in which they asked the Hindu ruler of the region to stay in Gujarat, and he agreed to live there under certain conditions. Among his conditions was: In the language, domination, and clothing of women, the Hindu customs should be considered, and also the means of war should be avoided. Accordingly, the Parsis accorded themselves perfectly to the culture and customs of the environment; this point was probably one of the reasons for the British approach toward them. Karaka writes in this regard: “It is a characteristic of the Persis that they have behaved appropriately to other peoples, even though their beliefs and customs are different, and they have adjusted themselves to the conditions, although the conditions were not according to their desire”. Jonathan Duncan, the British ruler of Mumbai at the beginning of the 19th century, criticized Muslims in a conversation with Abdul Latif Shushtari, comparing them to the Parsis, who easily adapted themselves to the custom and culture of the superior people: “What is the reason that wherever the monarchy of the Muslim exists or a sect of Muslims resides, their work is on the harshness ... unlike other religions which are smooth and gentle?" On the events of 986 AH / 1587 AD, Badayuni, the historian of the court of Jalaluddin Akbar has reported the presence of Zoroastrians from the city of Navsari in the Gujarat region in the court of this ruler and writes that this powerful ruler ordered that the fire always be kept lit in a certain place. The report shows that in the late 16th century, the city of Navsari near Surat was the main settlement of Zoroastrians in India and since the agricultural conditions of the region met their job and economic needs, they had not migrated to Surat. Although the Parsis lived in this port before the arrival of the Europeans, the increase in their number was closely related to the arrival of European companies in this city. The endeavour of European countries to penetrate east by sea led the Portuguese Vasco da Gama to become the first European sailor to set foot on Indian soil. Nehru reminds us that this first step was taken after the end of the Muslim rule over Andalusia in 1492 AD. Perhaps from the view of the new Iberian rulers, this move was revenge to conquer the East and spread Christianity in the face of the spread of Islam in Spain. Wasn't that the Portuguese paid special attention to the spread of Christianity in the East, and their violence of the Muslim merchants whom they called the Moors (Spanish Muslims) was unexampled? It is said that the intensity of the Portuguese violence was due to the superiority of the Muslims in trade, while part of it must be attributed to their dissatisfaction with the long Muslim rule in southwestern Europe. From the Europeans’ point of view, the port of Surat, in the south of Gujarat and on the bank of the navigable Tapi or Tapti River, about 30 km far from the Arabian Sea, was suitable for their ships to travel to India. The knowledge of European capitalists of the geographical location of Surat, which was connected with the Far East countries on the one hand and with the Iranian and Arab ports, on the other hand, encouraged them to build several factories in this port from the second decade of the 17th century. Also, the relative proximity of Surat to Deccan and Gujarat, the centers of cotton cultivation and production in India made the Europeans eager to build factories there. Then, the Portuguese, the Dutch, the French, and the British came to this port and each established a trading company in their own name. The location of Surat made this port the most commercially productive one in the 16th, 17th, and 18th centuries and was distinguished among Indian ports. This supremacy continued until the rise of Mumbai in the commercial arena, and then Surat was ignored. Although the British East India Company arrival in Surat after Portugal managed to repel the enemy with military force, the French financial bankruptcy in Surat automatically led to their removal from the port. The company, which ostensibly bore the name of the company and was in fact the British government with shareholders (mainly military personnel), after a while, took over the country's political destiny in addition to monopolizing India's trade. In this study, the reasons and methods of the East India Company's use of the Parsi society of India, as one of the tools to increase their influence in this land, as well as the type of cooperation of the Parsis with the British and its results for them are discussed. So far, no specific research has been done on this topic; however, numerous works related to the history of the Parsis, as well as writings related to the emergence and decline of the East India Company, contain scattered materials on the subject of this study. The manuscript of “Waqaye-i Hind” by Abdul Latif Shushtari at the beginning of the 19th century, which deals with the events in India, especially the island of Mumbai, has useful and relevant information in this regard. Shushtari, who was on behalf of the company, overseeing the affairs of Iranian businessmen in Mumbai, met daily with the island's Parsi leaders and recorded valuable notes of their relations with the company's leaders. The History of the Parsis, a work from the second half of the 19th century, also contains useful information on the subject of this article, due to the proximity of the author's era to the period of intimate relations between the Persians and the British. An article with the title Pyarsis and the British also contains notes on the relations between the Parsis and the East India Company which Hinnells published in 1978 in the journal of Kama Institute. 3- Materials and Methods have been the main sources of the author for writing this descriptive-analytical article. 4- Discussion of Results and Conclusions The British East India Company made its way to India later than Portugal, the Netherlands, and France in the early 17th century, but soon overtook European rivals and pursued its capitalist goals singly. In the meantime, the British needed the help of the natives of India to achieve their goals. People with abilities in business, sea voyages, knowledge of local products and facilities, knowledge of local leaders and celebrities, skills in intermediary in transactions and linguistics were among the characteristics of Parsis. On the other hand, the Zoroastrian community of India was eager to cooperate with the East India Company in order to be more successful in business, obtain various goods, and receive support during business trips. Although Parsis did not gain a high position in the company and even export goods directly to Europe, and the company's leaders viewed them as instrumental and a means of profit, in order to continue their cooperation, they were constantly provided with business opportunities and more income. The British acquisition of advanced technology in the textile industry, their progress in land and sea transportation, and entry into Asian markets, relying on the military in the 19th century, also had a positive impact on Parsis business. Their cooperation with the British for more than three centuries provided them with more wealth than they had imagined. The wealth they accumulated in the 18th century and the first half of the 19th century through various means, especially trade, was invested in the industry from the second half of this century. In the second half of the 19th century and the first half of the 20th century, they held half of the managerial and regulatory positions of Mumbai factories. They owned India's first steel plant. Some of them violated some of the moral limitations of Zoroastrianism and followed the British way of life to earn more money. At this time, Britain was their homeland. But the Parsis’ dependence on British capitalists also caused them some harm. In the late 19th century, the center of India's foreign trade was moved from the west of India, the center of Parsis’ gathering and life, to the east by the heads of companies; thus Parsis’ role in trade diminished. Opium exports from India to China also declined. New industries entered the world of Indian industry in 1900, and Parsis paid less attention to these industries due to the continued focus on cotton and fabric production. Together, these factors halted the economic growth of Parsis in the second half of the 20th century compared to the previous century. The Parsis’ close and intimate relations with the British also caused them cultural damages such as the loss of religious identity which has been considered and protested by some followers of this religion.